Assessing the Role of Indonesian Companies in Sectoral Economic Cooperation Between Indonesia and Timor-Leste: Opportunities and Challenges - Muhammad Indrawan Jatmika; Melvin A Jabar (Universitas Muhammadiyah Yogyakarta, 2024)
This study focuses on the significance of Indonesian companies in strengthening economic ties between Indonesia and Timor-Leste, considering both countries’ difficult historical backgrounds. The research employed a qualitative method, with a multiple-case study, to evaluate the participation of several Indonesian companies in Timor-Leste and gather data through literature studies and direct observation. The research revealed that Indonesian companies have played a crucial role in encouraging economic cooperation between the two nations, notably in the construction, energy, and agricultural sectors. These companies have made investments in Timor-Leste, created jobs, transferred technology, and contributed to infrastructural development. This research highlights the challenges faced by Indonesian businesses in Timor-Leste, such as a lack of skilled labor, a lack of capital, and complicated bureaucratic burdens. The analysis unveiled room for growth, even though Indonesian businesses have significantly benefited from economic cooperation between the two nations. This study recommends that, while keeping in mind the country’s intricate and delicate historical context, the Indonesian government and private sector have collaborated to address the difficulties faced by Indonesian businesses and to investigate new collaboration opportunities to strengthen the two countries’ economic ties.